2010
DOI: 10.1007/s12603-010-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Does chair type influence outcome in the timed “up and go” test in older persons?

Abstract: The use of a portable canvas chair with standardised specifications offers an acceptable alternative to the use of a 'standard' chair in assessments of fall risk using the TUG test in field settings where field workers are reliant on public transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…One hundred and eighteen subjects were recruited at a retirement centre and completed the timed Up and Go test on the collapsible chair and a standard chair. A detailed description of the chair and its use has been reported elsewhere 27 .…”
Section: Methodsmentioning
confidence: 99%
“…One hundred and eighteen subjects were recruited at a retirement centre and completed the timed Up and Go test on the collapsible chair and a standard chair. A detailed description of the chair and its use has been reported elsewhere 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The study required a portable chair that was easily transportable to use, to test lower limb power and balance of subjects during interviews in the subjects’ dwelling. An equipment validation study was conducted prior to the baseline survey to validate the portable chair that would be used in the study setting [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…As Bohannon et al 9 ) argue, differences in chairs may not preclude homogeneity. The TUG is performed in a variety of settings, such as in the community 2 ) , in care facilities 16 ) , and in hospitals 14 ) , because of its advantages in terms of the ease of measurement and lack of required specialized equipment. It is therefore plausible that TUG tests are not all performed in the same environment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Eekhof et al 15 ) measured TUG performance in older individuals using three different types of chairs with different seat heights and types and found that the effect of the chair type on the measurements was mild. Kalula et al 16 ) also examined whether two types of chairs (standard chair and folding chair) with the same seat height of 46 cm would change the time of the TUG in older individuals. They found no difference between the two chair types and reported that a portable folding chair could replace the standard chair.…”
Section: Introductionmentioning
confidence: 99%